Utility of Concentration Bleach Method and Fluorescent Auramine Rhodamine Staining in Diagnosis of Mycobactrium Tuberculosis on Formalin Fixed Tissue - Anjali Dhote; Vikas Kawishwar (New Horizons in Medicine and Medical Research Vol. 4, 2022)
Tuberculosis is one of humanity’s oldest diseases, as well as one of the deadliest epidemics. Mycobacterium tuberculosis infects one-third of the world’s population, with 9.6 million new cases reported each year. Tuberculosis kills almost 1.45 million people per year, making it the most common infectious disease in the world [1]. In developing nations like India, tuberculosis incidence has risen substantially in recent decades, with India having the highest burden of TB with an estimated incidence of 2.2 million cases out of the worldwide prevalence [2]. Also contributing to it is the human immunodeficiency virus. In India, about 2.1 million individuals are infected with HIV each year, and around 0.35 million people are sick with tuberculosis, which is the leading cause of mortality [1]. Given the severity of tuberculosis infection, early detection is critical in reducing morbidity and mortality. Many times we received clinical autopsies organ and one need to give a definitive cause of death in patient who died of tubercular features. Identification of mycobacterium is essential for a definitive diagnosis.